Analysis of the Influence of Motivation and Competence on Employee Commitment At XYZ Polytechnic of Jakarta - Caniago, Aspizain; Mardikawaty, Rini; Nurlia, Titim; Sopiah; Bambang Sutrisno, Supadi (MANAGER: Journal of Management and Administration Science, 2023)
This study's title is "Analysis of the Influence of provocation and capability on Hand Commitment at XYZ Polytechnic Jakarta." The purpose of this exploration is to ascertain the extent to which capability and provocation influence hand commitment at the XYZ Polytechnic Jakarta. Capability is an existent's capacity, mastery, and individual capacities, and responsibility is an existent's feeling of obligation for the work terrain. A strong internal drive is provocation. This study employs a quantitative exploration approach via a questionnaire with a total population of 85 and a sample size of 85 using the tale system for sample computation. The examination demonstrating this The t test shows that capability and allegiance have a significant impact on representative responsibility. This is shown by the tcount X1 of 0.364, the tcount X2 of 0.455. The determination measure( R2) is 0.496. This suggests that other variables that this study did not examine account for the remaining 50.4, while provocation and capability have an impact of 49.6.